CONSCIOUSNESS ABOUT ANIMAL WELFARE PRACTICES AMONG THE ANIMAL TRADERS - Dwivedi, Praduman Kumar; Singh , B P; Waila , Taruna (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
The study was carried out in Bareilly and Aligarh districts of Uttar Pradesh, to ascertain the consciousness of animal traders about animal welfare practices. A total of 100 animal traders , 25 from each selected animal markets. as respondents were selected The findings indicated little concern among animal traders about animal welfare practices.